المعوقات التنظيمية وعلاقتها بالفعالية التنظيمية للمؤسسة - حجايجي, ربيعة (جامعة الوادي university of Eloued, 2022)
الملخص: تهدف هذه الدراسة إلى التعرف على علاقة المعوقات التنظيمية بالفعالية التنظيمية للمؤسسة لدى مديرية الخدمات الجامعية بالوادي، ولتحقق هذا الهدف تم التطرق إلى مختلف المداخل النظرية والدراسات التي عالجتها في ضوء كل من أبعاد المعوقات التنظيمية المتمثلة في المعوقات الإدارية، والمادية، والفيزيقية، الاجتماعية، وفي هذا الصدد طرحنا التساؤل الرئيسي التالي: ما طبيعة العلاقة بين المعوقات التنظيمية والفعالية التنظيمية للمؤسسة؟ وتفرعت عنه التساؤلات التالية: - ما طبيعة العلاقة بين المعوقات الإدارية والفعالة التنظيمية للمؤسسة؟ - ما طبيعة العلاقة بين المعوقات المادية والفعالية التنظيمية للمؤسسة؟ - ما طبيعة العلاقة بين المعوقات الفيزيقية والفعالية التنظيمية للمؤسسة؟ - ما طبيعة العلاقة بين المعوقات الاجتماعية والفعالية التنظيمية للمؤسسة؟ وقد تم الاعتماد على المنهج الوصفي لأنه الأنسب لهاته الدراسة، وشملت الدراسة على عينة مكونة من 53 عامل أي ما يعادل 6% من موظفي مديرية الخدمات الجامعية بالوادي، كما تم الاعتماد على أداتي الاستبيان والمقابلة لجمع البيانات. Résumé : فرنسية أو إنجليزية This study aims to identify the relationship of organization obstacles with the organizational effeteness of the institution at the directorate of university services in the El Oued. In this regard, we asked the following main question: What is the nature of the relationship between organizational effectiveness of the institution? The following questions emerged from it: - What is the nature of the relationship between administrative obstacles and organizational effectiveness of the institution? - What is the nature of the relationship between physical obstacles and organizational effectiveness of the institution? - What is the nature of the relationship between physical obstacles and organizational effectiveness of the institution? - What is the nature of the relationship between social obstacles and organizational effectiveness of the institution? The descriptive approach was relied upon because it is the most appropriate for this study. The study included a sample of 53 workers, equivalent to 6 % of the employees of the directorate of university services in the El Oued. The questionnaire and interview tools were also used to collect data.
دراسة ميدانية علي عينة من عمال مديرية الخدمات الجامعية بالوادي
مذكرة ماستر علم الاجتماع تخصص علم اجتماع تنظيم وعمل
Keywords: المعوقات التنظيمية، الفعالية التنظيمية; Obstacles organisationnels, efficacité organisationnelle; Organizational obstacles, organizational effectiveness